Effect on Nail Structure and Transungual Permeability of the Ethanol and Poloxamer Ratio from Cyclodextrin-Soluble Polypseudorotaxanes Based Nail Lacquer - Elena Cutrín-Gómez; Soledad Anguiano-Igea; M. Begoña Delgado-Charro; José Luis Gómez-Amoza; Francisco J. Otero-Espinar (MDPI AG, 2018)
Aqueous-based nail lacquers have shown potential in promoting the diffusion of drugs into the nail. In our laboratory, we have recently developed a transungual delivery system based on an aqueous dispersion of cyclodextrin-poloxamer soluble polypseudorotaxanes, supramolecular host−guest assemblies that improves the drug permeation into the nail. However, the high-water content and the rheological and adhesive properties of this lacquer negatively affect properties that play a fundamental role in the patients’ acceptance such as stickiness, nail film formation or drying rate, properties. In this work, we have optimized the composition of these lacquers to improve these properties whilst maintaining good drug permeation profiles. Incorporating ethanol into the vehicle and reducing the proportion of Poloxamer 407 (PL), provided a good strategy. The use of hydro-ethanolic mixtures (>50% ethanol) and the reduction of the poloxamer concentration significantly improved the lacquer drying speed by reducing the stickiness and promoting film formation on the nail surface. Additionally, in a surprising way, the use of hydro-ethanolic vehicles further enhanced the permeation of ciclopirox olamine and clobetasol propionate, used for the treatment of onychomycosis and nail psoriasis respectively, into the nail and hooves.